Peculiarities of Designing the Frame of a Universal Container Made of Rectangular Pipes - Gerlici, Juraj; Lovska, Alyona; Pavliuchenkov, Mykhailo; Kravchenko, Oleksandr (Communications - Scientific Letters of the University of Zilina, 2024)
The features of designing the frame of a universal container made of square pipes are presented in this paper. The two frame loading schemes are taken into account: the effect of vertical loading on the container frame when it is lifted by the upper corner fittings (I loading mode); the effect of longitudinal loading on the frame during transportation by the rail transport (II loading mode). Mathematical modeling was performed to determine the longitudinal loading acting on the container in the II loading mode. The determined acceleration is taken into account when constructing the schemes of force factors that arise in the frame. The strength of the frame was calculated using the finite element method, which was implemented in SolidWorks Simulation. The conducted research could contribute to creation of recommendations and developments regarding the design of modern structures of modular vehicles.
Keywords: container; container frame; container loading; container strength; container transportation